Student Perceptions on the Use of Warming-Up Activities to Increase Learners’ Motivation In English Classes - Faizah, Nailah; Safriani, Afida; Kurniasari, Aulia Drifani (ICONELT, 2024)
A major challenge in modern education is maintaining student attention, which has been found to diminish considerably faster than in previous decades. Considering these challenges, educators must incorporate imaginative and captivating activities to attract and maintain learners’ focus. One effective method is to incorporate warming-up activities at the start of lessons to enhance student motivation and engagement. This study aims to investigate high school learners’ views on the effectiveness of these activities in English classes. Utilizing a quantitative research design, data were gathered through structured questionnaires distributed to 79 randomly selected 10th and 11th-grade learners from a public school in Sidoarjo. The questionnaire addressed two key areas: the implementation of warming-up activities in English classes and the effectiveness of warming-up activities in Increasing motivation in English classes. The results indicated that most learners find warming-up activities advantageous for shifting into a learning mindset, increasing classroom engagement, and creating a positive learning environment. Furthermore, learners reported heightened motivation and participation when these activities were included. The study concludes that incorporating warming-up exercises into English lessons is essential for enhancing student motivation and should be regarded as a vital component of effective teaching strategies in EFL classrooms.